Agent-Oriented Software Engineering IX 9th International Workshop, AOSE 2008, Estoril, Portugal, May 12-13, 2008, Revised Selected Papers - Luck, Michael; Gomez-Sanz, Jorge J. (Programming and Software Engineering,, 2009)
Software architectures that contain many dynamically interacting components, each with its own thread of control, engaging in complex coordination protocols, are difficult to correctly and efficiently engineer. Agent-oriented modelling techniques are important for the design and development of such applications. This book provides a diverse and interesting overview of the work that is currently being undertaken by a growing number of researchers in the area of Agent-Oriented Software Engineering. The papers represent a state-of-the-art report of current research in this field, which is of critical importance in facilitating industry take-up of powerful agent technologies. This volume constitutes the thoroughly refereed post-conference proceedings of the 9th International Workshop on Agent-Oriented Software Engineering, AOSE 2008, held in Estoril, Portugal, in May 2008 as part of AAMAS 2008. The 20 revised full papers were carefully selected from 50 initial submissions during two rounds of reviewing and improvement. The papers have been organized into four sections on: multi-agent organizations, method engineering and software development processes, testing and debugging, as well as tools and case studies.